Updates on Inflammatory Molecular Pathways Mediated by ADAM17 in Autoimmunity - Margherita Sisto; Sabrina Lisi (Cells)
ADAM17 is a member of the disintegrin and metalloproteinase (ADAM) family of transmembrane proteases with immunoregulatory activity in multiple signaling pathways. The functional ADAM17 is involved in the shedding of the ectodomain characterizing many substrates belonging to growth factors, cytokines, receptors, and adhesion molecules. The ADAM17-dependent pathways are known to be crucial in tumor development and progression and in the modulation of many pathological and physiological processes. In the last decade, ADAM17 was considered the driver of several autoimmune pathologies, and numerous substrate-mediated signal transduction pathways were identified. However, the discoveries made to date have led researchers to try to clarify the multiple mechanisms in which ADAM17 is involved and to identify any molecular gaps between the different transductional cascades. In this review, we summarize the most recent updates on the multiple regulatory activities of ADAM17, focusing on reported data in the field of autoimmunity.